Mental health of older people in social isolation: the role of physical activity at home during the COVID-19 pandemic - da Cruz W.M.* (2022)
© 2021, The Author(s), under exclusive licence to Springer-Verlag Italia S.r.l., part of Springer Nature.The COVID-19 pandemic involves a new coronavirus characterized by a respiratory disease resulting from an infection with severe acute respiratory syndrome by coronavirus 2 (SARS-CoV-2). The severity and fatality of COVID-19 are directly related to age and immunocompromised states, with older adults making up the vast majority of cases. The elderly with a higher risk of serious complications due to COVID-19 and deaths are also the group most susceptible to the damage of social isolation, impacting on mental health, resulting in a more sedentary lifestyle, and health problems due to several causes, implying need for greater attention, care and protection. Physical activity has shown excellent results for mental health, being used in different treatments and populations, when considering the elderly, one of the ways to mitigate this impact on mental health is the practice of physical activity. Here, we discuss the impacts of social isolation on mental health and the role of physical activity and exercise in the homes of the elderly as a way to protect the spread of other diseases from all causes during the COVID-19 pandemic period. To this end, we discuss some possibilities that can be used by the elderly in the period of social isolation, to the point of remaining active within their homes.